THE INFLUENCE OF FINANCIAL LITERACY, DIGITAL LITERACY, AND BUSINESS KNOWLEDGE ON UMKM DEVELOPMENT MEDIATED BY INNOVATION - Tarigan, Ruth Abigail; Suparno, Suparno; Wibowo, Agus (Universitas Islam Malang, 2025)
This study aims to analyze the effect of financial literacy, digital literacy, and business knowledge on the development of Micro, Small, and Medium Enterprises (MSMEs), with innovation as a mediating variable. Data were collected from MSME respondents in Central Jakarta using a structured survey. The analysis method used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results showed that financial literacy, digital literacy, and business knowledge have a significant influence on innovation and development of MSMEs. Directly, financial literacy affects innovation with a t-count value of 14.715 (p-value 0.000) and MSME development with a t-count value of 7.568 (p-value 0.000). Digital literacy shows a significant influence on innovation (t-count 15.082; p-value 0.000) and MSME development (t-count 8.654; p-value 0.000). Business knowledge also affects innovation (t-count 12.918; p-value 0.000) and MSME development (t-count 7.477; p-value 0.000). Testing the indirect effect through innovation shows significant results. Financial literacy influences MSME development through innovation with a t-count of 2.205 (p-value 0.022). Digital literacy shows a significant indirect influence on MSME development through innovation (t-count 2.197; p-value 0.023). Business knowledge is also shown to influence MSME development indirectly through innovation (t-count 2.195; p-value 0.023). Innovation is proven to be a mediator that strengthens the relationship between the three independent variables and MSME development. This research provides practical contributions in the form of recommendations for improving financial literacy, digital technology adoption, and better business understanding to support MSME innovation and growth. In addition, innovation is a strategic key in creating competitiveness and business sustainability in the midst of modern economic challenges.